1990
DOI: 10.1136/bmj.301.6755.790
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral loss in young women with amenorrhoea.

Abstract: offered exposure to positive suggestions during general anaesthesia. This would give patients the beneficial effect of the positive suggestions and protect them from the negative effects of "hearing" adverse or negative comments. Main outcome measure-Bone mineral density in the lumbar spine (L1-L4) as measured by dual energy x ray absorptiometry.Results-The amenorrhoeic group showed a mean reduction in bone mineral density of 15% (95% confidence interval 12% to 18%) as compared with controls (mean bone mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(54 citation statements)
references
References 33 publications
2
50
0
2
Order By: Relevance
“…Late menarche and menstrual irregularity are also been showed to be important risk factors for osteoporosis development [25]. In our study, we highlighted a reduction in bone mineral density during following up of POI women.…”
Section: Discussionsupporting
confidence: 60%
“…Late menarche and menstrual irregularity are also been showed to be important risk factors for osteoporosis development [25]. In our study, we highlighted a reduction in bone mineral density during following up of POI women.…”
Section: Discussionsupporting
confidence: 60%
“…Because statistical analysis elsewhere has yielded a clinically significant increased risk for fracture with a discrepancy of 7% among postmenopausal women (14), our observed magnitude of difference in BMD among adolescent DMPA users, if irreversible, may increase eventual risk for fractures. No studies to date have evaluated DMPA use and fracture risk in adolescent girls.…”
Section: Discussionmentioning
confidence: 59%
“…In past basic training studies, menstrual irregularities have also been shown to increase injury risk [29,43,96]. Investigations of female athletes have also indicated that those with menstrual irregularities have a higher injury incidence of musculoskeletal injuries [97], especially with bone stress injuries [97-99], and that these athletes take longer to recover from their injuries [100]. It has been hypothesized that amenorrhea results in hormonal changes, especially lower estrogen levels, which leads to a reduction in bone mineral density and increasing likelihood of fracture [97,99-101].…”
Section: Discussionmentioning
confidence: 99%